2023
DOI: 10.3390/nu15061435
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Analysis of Food Insecurity and Body Mass Index with Income and Grocery Store Density in a Diverse Sample of Adolescents and Young Adults

Abstract: Food insecurity occurs when a household lacks consistent access to food and is more prevalent in ethnic and racial minority populations. While there has been a proliferation of research linking food insecurity to obesity, these findings are mixed. It may be helpful to consider some additional geographic factors that may be associated with both factors including socioeconomic status and grocery store density. The purpose of the current study aimed to examine spatial relationships between food insecurity and SES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…The complex interplay of consumer behaviours and food access is not just about preferences or marketing; it also has significant social implications. Research by Buscemi et al (2023) sheds light on how food insecurity is intricately linked with socioeconomic status and geographical location. The study found that individuals with high levels of food insecurity are often confined to areas with low median incomes, corroborating the need to consider social and economic factors in food access strategies.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…The complex interplay of consumer behaviours and food access is not just about preferences or marketing; it also has significant social implications. Research by Buscemi et al (2023) sheds light on how food insecurity is intricately linked with socioeconomic status and geographical location. The study found that individuals with high levels of food insecurity are often confined to areas with low median incomes, corroborating the need to consider social and economic factors in food access strategies.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Berbeda halnya dengan ilmu geografi murni, ilmu geografi terapan lebih mengutamakan teori, teknik, dan metode dari ilmu geografiyang ada untuk menelaah, mengevaluasi, dan memberikan solusi serta implementasinya atas permasalahan empiris yang terjadi [3]. Sekarang ini, relevansi nilai-nilai terapan dari ilmu geografi semakin terlihat jelas seiring dengan banyaknya kondisi permasalahan yang terjadi, contohnya: bencana alam [4][5], masalah lingkungan [6][7], permasalahan ruang terbuka hijau [8], hingga kemanusiaan [9][10]. Dalam kaitannya dengan dunia pendidikan, terutama pada lingkungan SMA, ilmu geografi baru diajarkan dan berdiri sendiri sebagai mata pelajaran wajib, berbeda halnya ketika di SD dan SMP yang mana terintegrasi dengan ilmu lainnya sebagai ilmu pengetahuan sosial.…”
Section: Pendahuluanunclassified
“…Populations in food deserts often have limited access to fresh fruits and vegetables, leading to diets high in (ultra)-processed and energy-dense foods [2]. This dietary pattern is strongly associated with increased risks of obesity, a finding that is consistently reported in public health [22][23][24]. Obesity, in turn, is a known risk factor for various metabolic disorders, including type 2 diabetes, as established in epidemiological studies [25][26][27].…”
Section: Introductionmentioning
confidence: 98%